2018
DOI: 10.3390/beverages4040073
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Response Relationships for Vanilla Flavor and Sucrose in Skim Milk: Evidence of Synergy

Abstract: Regarding cross-modality research, taste-aroma interaction is one of the most studied areas of research. Some studies have reported enhancement of sweetness by aroma, although it is unclear as to whether these effects actually occur: depending on the cognitive strategy employed by panelists, the effects may disappear, e.g., forcing panelists into an analytical strategy to control for dumping may not be able to reveal perceptual interactions. Previous studies have largely focused on solutions and model foods, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 64 publications
7
32
0
Order By: Relevance
“…The vanilla aroma was in both matrices found to enhance sweet taste with increasing vanilla aroma concentrations (Tables 3 and 4), at least up to 1 mL/kg which was the maximum concentration tested in this study. As mentioned, this is in accordance with an abundance of previous literature demonstrating that addition of vanilla aroma increased sweet taste perception [6,7,16,17,[35][36][37][38][39]. However, in terms of vanilla concentration, few authors have studied the effect of vanilla aroma concentration on sweet taste intensity.…”
Section: The Cross-modal Effect Of Vanilla Aroma On Sweet Taste Intensupporting
confidence: 88%
See 2 more Smart Citations
“…The vanilla aroma was in both matrices found to enhance sweet taste with increasing vanilla aroma concentrations (Tables 3 and 4), at least up to 1 mL/kg which was the maximum concentration tested in this study. As mentioned, this is in accordance with an abundance of previous literature demonstrating that addition of vanilla aroma increased sweet taste perception [6,7,16,17,[35][36][37][38][39]. However, in terms of vanilla concentration, few authors have studied the effect of vanilla aroma concentration on sweet taste intensity.…”
Section: The Cross-modal Effect Of Vanilla Aroma On Sweet Taste Intensupporting
confidence: 88%
“…When stimuli in one sensory modality affect the perception of stimuli in another modality, it is called a cross-modal interaction [9], e.g., when the addition of aroma affects the perception of sweet taste [6,[10][11][12][13][14][15][16][17]. The effect of aromas on taste perception is, among other things, dependent on the specific aromas used [16,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among taste attributes, only sweet taste was found to exhibit a significant sample difference, with RMAs D, E, and F containing lower amounts of sugar (Table ) exhibiting lower sweetness intensities than RMAs A, B, C, and/or G. In particular, RMA G that included vanilla flavor was rated as having a greater sweetness intensity, possibly due to vanilla flavor being considered congruent to sweet taste and thereby increasing sweetness intensity in the RMA G. Such a congruent odor‐induced sweetness enhancement had been observed in earlier psychophysical and neuroimaging studies (Seo et al, ; Small et al, ; Small & Prescott, ; Oliveira et al, ; Wang, Hayes, Ziegler, Roberts, & Hopfer, ). Wang et al () conducted a dose–response study of fluid milk to determine cross‐modal interactions between a sweet tastant (sucrose) and a congruent odor (vanilla extract). In their study, an elevated vanilla concentration resulted in a slight but significant sweetness enhancement.…”
Section: Resultsmentioning
confidence: 51%
“…In their study, an elevated vanilla concentration resulted in a slight but significant sweetness enhancement. Conversely, increasing sucrose concentration was found to lead to an increased vanilla flavor intensity (Welge‐Lüssen, Husner, Wolfensberer, & Hummel, ; Wang et al, ). In another study using a Temporal Check‐All‐That‐Apply (TCATA) method, Oliveira et al () showed that citation frequency of a vanilla flavor attribute decreased with reduced level of added sugar in chocolate‐flavored milk.…”
Section: Resultsmentioning
confidence: 99%